Mechanical properties of achilles tendon in relation to various sport activities of collegiate athletes - Kurihara, T.; Sasaki, R.; Isaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate whether mechanical properties of Achilles tendon adapt to the mechanics of diffrent sport activities. Subjects included thirty-five male collegiate track and field athletes (Sprinters, Long distance runners, Jumpers), swimmers, and non-athletes (Controls). The elongation of the Achilles tendon during isometric voluntary plantar flexion contraction was measured. Jumpers and swimmers displayed larger elongation, strain, tendon force and stress of the Achilles tendon when compared to long distance runners and controls. However, the stiffness and Young`s modulus of the Achilles tendon were not significantly different between groups. These results suggested that mechanical properties of the Achilles tendon were unchanged with load characteristics of each sport activity.